Heat resistant titanium-based composite material and heat resistant titanium-based composite material rod and method for producing the same
Patent Information
- Application Number
- CN202611213345.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
AI Technical Summary
本发明要解决现有技术中存在的耐热钛基复合材料棒材制备周期长、制备过程中坯料易开裂、棒材成材率低的技术问题
1、本发明通过合理配比Al、Sn、Zr、Mo、Nb、Ta、Si、B等元素,并设定(Al+Sn/3)≤8及Nb+Ta≤2.5的约束条件,实现了多种析出相(如TiB、硅化物、α2相等)的协同强化。适度提高铌、钽等β稳定元素的含量,有效改善了钛基复合材料的塑性及热加工工艺性,获得了较好的强塑性匹配。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat-resistant materials technology, and more specifically, to a heat-resistant titanium-based composite material and heat-resistant titanium-based composite material rods and their preparation methods. Background Technology
[0002] The aerospace industry has an increasingly urgent need for high-performance, lightweight, and heat-resistant structural materials. Currently, the maximum service temperature of high-temperature titanium alloys is typically below 650°C. As the service temperature continues to increase, the material composition becomes more complex, leading to increasingly prominent problems such as increased manufacturing difficulty and challenges in coordinating and matching overall performance.
[0003] Titanium-based composites incorporate ceramic reinforcing phases into a titanium alloy matrix. Utilizing the load-bearing strengthening effect of these reinforcing phases, titanium-based composites can achieve an ideal balance of strength and plasticity within the same temperature range through a relatively simple composition system and processing technology. However, current research on titanium-based composite rods is limited. For example, invention patent CN111020414A discloses a method for preparing short-fiber reinforced high-temperature titanium alloy rods for 700-750℃. This method combines traditional titanium alloy hot working techniques, employing β-phase region forging and multi-stage upsetting and drawing forging below the β-phase transformation point to prepare the rods, and then controlling the properties through solution aging heat treatment.
[0004] However, due to the introduction of hard, difficult-to-deform ceramic reinforcing phases into titanium-based composites, their deformation resistance during hot deformation is significantly higher than that of traditional titanium alloys. If traditional titanium alloy bar fabrication processes are used, the billet is highly susceptible to cracking during bar fabrication, resulting in low bar yield and high material development costs. This problem is exacerbated by smaller bar sizes and higher reinforcing phase content, leading to even lower yields. Given these shortcomings of existing technologies, it is necessary to develop a novel heat-resistant titanium-based composite material and a short-process, high-yield bar fabrication method, focusing on material composition design and optimization of bar fabrication processes. Summary of the Invention
[0005] (a) Technical problems to be solved The present invention aims to solve the technical problems of long preparation cycle, easy cracking of billet during preparation, and low yield of heat-resistant titanium-based composite rods in the prior art.
[0006] (II) Technical Solution To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a heat-resistant titanium-based composite material, wherein the chemical composition of the heat-resistant titanium-based composite material comprises the following components by mass percentage: Al: 6.4~7.0%; Sn: 2~4%; Zr: 3~5%; Mo: 0.4~0.8%; Nb: 0.9~1.6%; Ta: 0.9~1.6%; Si: 0.25~0.4%; B: 0.3~0.7%; O: 0.06~0.12%; C: ≤0.1%; balance Ti; wherein the content of each component satisfies the following constraints: (Al + Sn / 3) ≤ 8, and Nb + Ta ≤ 2.5%. The solid solution strengthening of Al, Sn, and Zr, along with the synergistic effect of silicides formed by Si and B and the TiB reinforcing phase, ensures the high-temperature strength of the composite material above 650℃. The constraint of (Al+Sn / 3)≤8 avoids excessive α-stabilizing elements that lead to brittleness and ensures room temperature plasticity. The constraint of Nb+Ta≤2.5 controls the total amount of β-stabilizing elements to avoid microstructure instability. At the same time, the appropriate addition of Nb and Ta improves hot working plasticity, giving the material both high strength and good hot deformation ability.
[0007] Preferably, the Nb content in the composite material is 0.9–1.44 wt%, the Ta content is 0.9–1.48 wt%, and the mass ratio of Nb to Ta satisfies Nb / Ta = 0.5–1.5. By optimizing the Nb to Ta ratio, the β-stabilizing effect and solid solution strengthening effect are further balanced, avoiding component segregation or uneven microstructure caused by excessive single element, resulting in more uniform deformation resistance during hot working, reducing the risk of forging cracks, and improving the yield of bar stock.
[0008] Preferably, the B content ranges from 0.35 to 0.50 wt%, and the TiB reinforcing phase is dispersed in the matrix in the form of whiskers. The aspect ratio of the whiskers is controlled between 3 and 10 after forging and hot working. Within this range, B can form an appropriate amount of TiB whiskers, which play a dual role in load transfer and grain refinement. The aspect ratio of the whiskers is controlled between 3 and 10, which ensures sufficient reinforcement while avoiding breakage or stress concentration of excessively long whiskers during deformation, thus balancing high-temperature strength and plasticity.
[0009] Secondly, the present invention also provides a method for preparing a heat-resistant titanium-based composite material rod, wherein the material of the rod is the aforementioned heat-resistant titanium-based composite material, and the preparation method includes the following steps: S1. The components of the heat-resistant titanium-based composite material are uniformly mixed in a mixer, pressed into single electrodes, and welded together to form a melting electrode. The titanium-based composite material ingot is prepared by at least three vacuum self-consuming arc melting processes. The ingot is then subjected to riser, ingot bottom sawing, and peeling treatment to obtain the finished ingot. S2. The finished ingot obtained in step S1 is subjected to 1 to 2 forging cycles at 1150℃~1200℃ using a high-speed forging machine. The holding time is the diameter of the finished ingot × 0.8 min / mm. Each forging cycle adopts the upsetting and drawing process and the total forging ratio of upsetting and drawing in a single forging cycle is not less than 7.0. The deformation speed is controlled at 20~50 mm / s, and the final forging temperature is not lower than 900℃. After forging, it is air-cooled to obtain the forged billet. S3, the forged billet obtained in step S2 is subjected to T β -60℃~T β The forging process involves 1 to 4 forgings within a temperature range of +100℃, with 2 to 6 deformation passes per forging. The deformation amount per pass is controlled at 5% to 30%, and the final forging temperature is not lower than 800℃. This process yields semi-finished bars, which are then surface-machined to obtain small-diameter bars with a diameter of 100mm or less. S4. Heat-treat the small-sized rods obtained in step S3, and then machine them to obtain heat-resistant titanium-based composite material rods.
[0010] Preferably, in step S2, the initial forging temperature of the billet forging is 1150℃, and two upsetting and drawing processes are performed. The total forging ratio of each upsetting and drawing process is 7.0 to 7.5, the deformation speed is 30 to 40 mm / s, and the final forging temperature is not lower than 920℃. After forging, the billet is air-cooled to room temperature before being reheated in a furnace for the next upsetting and drawing process. Performing two large deformation processes at a temperature slightly higher than the β phase transformation point, combined with a moderate deformation speed, can effectively break up the as-cast dendritic structure and TiB clusters, while avoiding overheating that could lead to abnormal grain growth. A final forging temperature ≥920℃ ensures that the deformation is completed in the β single-phase region, which is beneficial for obtaining a uniform β recrystallization structure and provides a good microstructure basis for subsequent precision forging.
[0011] Preferably, in step S3, the precision forging is performed using a radial precision forging machine at a forging temperature of 1050℃~1120℃, with two forging passes, each forging pass consisting of 4~5 passes, and the deformation per pass controlled at 10%~25%, with a final forging temperature not lower than 820℃; the resulting small-diameter bar has a diameter of Φ30mm~Φ100mm. The triaxial compressive stress state applied by the radial precision forging machine is beneficial for suppressing cracking at the interface between the TiB reinforcing phase and the matrix; performing multiple small deformation passes within the two-phase region (α+β) temperature range can gradually refine the α-lamellae and promote the oriented alignment of TiB whiskers, ultimately obtaining small-diameter bars with uniform microstructure and excellent surface quality.
[0012] Preferably, in step S4, the heat treatment is a single-stage annealing or a solution aging treatment. The single-stage annealing includes the following steps: holding at 600℃~850℃ for 4~8 hours followed by air cooling; the solution aging treatment includes the following steps: first at T… β -120℃~T βAfter holding at +80℃ for 0.5–2 hours, air cool or water quench. Then, hold at 600℃–800℃ for 4–8 hours followed by air cool. Single-stage annealing can eliminate processing stress and stabilize the microstructure, making it suitable for scenarios with moderate strength requirements and a focus on process simplification. Solution aging treatment fully dissolves alloying elements through high-temperature solution treatment, followed by aging precipitation of fine silicides and α2 phase, achieving secondary strengthening. This can significantly improve high-temperature creep and endurance performance, allowing users to flexibly choose according to actual service conditions.
[0013] Preferably, in step S4, the solution aging treatment specifically includes the following steps: holding at 1000℃~1050℃ for 1 hour followed by water quenching, then heating to 700℃ and holding for 4 hours before air cooling; or holding at 1025℃ for 1.5 hours followed by furnace cooling, then heating to 1010℃ and holding for 1 hour followed by water quenching, then heating to 700℃ and holding for 4 hours before air cooling. The first process is a single solution treatment + aging, which is simple to operate and can obtain good comprehensive performance at room temperature and high temperature; the second process adopts a double solution treatment of furnace cooling pre-precipitation + subsequent solution treatment, which can further optimize the α-lamellae morphology and precipitate distribution, making the high-temperature strength and plasticity more well matched.
[0014] Thirdly, the present invention provides a heat-resistant titanium-based composite material rod prepared by the method described above. The finished rod has a specification of no more than Φ100mm, an elongation at room temperature of no less than 8%, a tensile strength at 650℃ of no less than 650MPa and an elongation at break of no less than 20%, and a reduction of area of no less than 55%.
[0015] (III) Beneficial Effects The above-described technical solution of the present invention has at least the following advantages: 1. This invention achieves synergistic strengthening of multiple precipitated phases (such as TiB, silicides, α2 phases, etc.) by rationally proportioning elements such as Al, Sn, Zr, Mo, Nb, Ta, Si, and B, and setting constraints of (Al+Sn / 3)≤8 and Nb+Ta≤2.5. Appropriately increasing the content of β-stabilizing elements such as niobium and tantalum effectively improves the plasticity and hot workability of titanium-based composite materials, achieving a better balance between strength and plasticity.
[0016] 2. This invention addresses the grain refinement characteristics of particle-reinforced titanium matrix composites by designing a short-process manufacturing procedure of "bill forging + precision forging." By precisely controlling the forging temperature and deformation amount, the size of the TiB reinforcing phase and the matrix grains are refined, and the distribution of the reinforcing phase is optimized. Compared with traditional multi-stage deformation processes, this method significantly reduces the number of forging stages, shortens the processing flow, effectively avoids billet cracking, and greatly improves the yield of small-diameter bars.
[0017] 3. This invention, through the combination of the above-mentioned component design and short-process preparation, and by controlling the matrix microstructure through appropriate heat treatment processes (single-stage annealing or solution aging), ultimately obtains heat-resistant titanium-based composite rods that achieve a good match between thermal strength and ductility. The rod properties can reach: room temperature ductility >8%, tensile strength at 650℃ >650 MPa, and elongation at 650℃ >20%, which can meet the stringent requirements of aerospace and other fields for high-performance lightweight heat-resistant structural materials. Detailed Implementation
[0018] To make the technical problems, solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0019] The specific implementation of the present invention will be described in more detail below with reference to specific embodiments: Example 1 The heat-resistant titanium-based composite material provided in this embodiment is made of Al: 6.69%, Sn: 2.83%, Zr: 4.04%, Mo: 0.59%, Si: 0.33%, Nb: 1.44%, Ta: 0.98%, B: 0.35%, and the balance Ti by weight.
[0020] The preparation method of heat-resistant titanium-based composite rods includes the following steps: (1) Vacuum consumable electrode melting: First, the raw material composition of the heat-resistant titanium-based composite material is calculated to determine the required element content for the ingot. The raw materials are uniformly mixed in a mixer, then pressed into single electrodes and welded into melting electrodes. The titanium-based composite material ingot is prepared by three vacuum consumable electrode melting processes. After riser, ingot bottom sawing, and peeling treatments are performed on the ingots obtained from the three vacuum consumable electrode melting processes, a cylindrical ingot with a diameter of φ of 380mm is obtained.
[0021] (2) Forging: The ingot obtained in step (1) is subjected to two forging cycles at 1150℃ using a high-speed forging machine. The total forging ratio of upsetting and drawing in each cycle is 7.2. The deformation speed is controlled at 20~50mm / s. The final forging temperature is not lower than 900℃. After forging, the ingot is air-cooled to obtain the forged billet after forging.
[0022] (3) Precision forging: The forging billet obtained in step (2) is precision forged twice at 1050℃~1120℃, with four deformation passes per pass. The deformation amount per pass is controlled at 5%~30%, and the final forging temperature is not lower than 800℃. The precision forged bar is then machined and subjected to other surface treatments to obtain a 60mm finished bar.
[0023] (4) Heat treatment: The finished bars obtained in step (3) were subjected to solution aging heat treatment at (1000℃~1050℃) for 1h / WQ + 700℃ / 4h / AC, and heat treatment at 1025℃ / 1.5h / FC + 1010℃ / 1h / WQ + 700℃ / 4h / AC. After heat treatment, small-sized heat-resistant titanium-based composite material bars with good matching of room and high temperature properties were obtained.
[0024] Example 2 The difference between this embodiment and Example 1 is that the heat-resistant titanium-based composite material used consists of Al: 7%, Sn: 2.1%, Zr: 3.5%, Mo: 0.81%, Si: 0.24%, Nb: 0.99%, Ta: 1.48%, B: 0.3%, and the balance Ti.
[0025] (1) Melting: First, the batching calculation was performed according to the composite material composition of Example 1 to determine the required element content for the ingot. The raw materials were uniformly mixed in a mixer, then pressed into single electrodes and welded into melting electrodes. Titanium-based composite material ingots were prepared by three-stage vacuum consumable electrode melting. After riser, ingot bottom sawing and peeling treatments were performed on the ingots obtained by three-stage vacuum consumable electrode melting, cylindrical ingots with a diameter of φ of 380mm were obtained.
[0026] (2) Upsetting and drawing forging: The ingot obtained in step (1) is subjected to one heat at 1150℃ using a high-speed forging machine. The total upsetting and drawing ratio is 7.2, the deformation speed is controlled at 20~50mm / s, the final forging temperature is not lower than 900℃, and the forging is air-cooled after forging to obtain the forged billet after upsetting.
[0027] (3) Precision forging: The intermediate forging billet obtained in step (2) is precision forged twice at 1050℃~1120℃, with 5 deformation passes per pass, and the deformation amount per pass is controlled at 5%~30%, and the final forging temperature is not lower than 800℃. The precision forged bar is then machined and other surface treatments to obtain a 60mm finished bar.
[0028] (4) Heat treatment: The finished bars obtained in step (3) were subjected to solution aging heat treatment at (1010℃~1050℃) for 1h / WQ + 700℃ / 4h / AC, and heat treatment at 1025℃ / 1.5h / FC + 1010℃ / 1h / WQ + 700℃ / 4h / AC. After heat treatment, small-sized heat-resistant titanium-based composite material bars with good matching of room and high temperature properties were obtained.
[0029] Example 3 The difference between this embodiment and Example 1 is that the heat-resistant titanium-based composite material used consists of Al: 6.4%, Sn: 3.2%, Zr: 4.9%, Mo: 0.5%, Si: 0.3%, Nb: 0.9%, Ta: 1.0%, B: 0.5%, and the balance Ti.
[0030] Its preparation method is basically the same as that in Example 1.
[0031] Performance testing The mechanical properties of the rods prepared in Example 1 were tested, and the results are shown in Table 1.
[0032] Table 1 Mechanical properties of materials in Example 1 As shown in the table above, the heat-resistant titanium-based composite rods prepared using the technical solution of this invention have an elongation at room temperature of not less than 8%, a tensile strength at 650℃ of not less than 650MPa and an elongation at 650℃ of not less than 20%, and a reduction of area of not less than 55%, achieving excellent high-temperature strength and ductility matching.
[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A heat-resistant titanium-based composite material, characterized in that, The chemical composition of the heat-resistant titanium-based composite material consists of the following components by mass percentage: Al: 6.4~7.0%; Sn: 2~4%; Zr: 3~5%; Mo: 0.4~0.8%; Nb: 0.9~1.6%; Ta: 0.9~1.6%; Si: 0.25~0.4%; B: 0.3~0.7%; O: 0.06~0.12%; C: ≤0.1%; balance Ti; wherein the content of each component satisfies the following constraints: (Al + Sn / 3) ≤ 8, and Nb + Ta ≤ 2.5%.
2. The heat-resistant titanium-based composite material as described in claim 1, characterized in that, The composite material contains 0.9–1.44 wt% Nb and 0.9–1.48 wt% Ta, and the mass ratio of Nb to Ta satisfies Nb / Ta = 0.5–1.
5.
3. The heat-resistant titanium-based composite material as described in claim 1, characterized in that, The B content ranges from 0.35 to 0.50 wt%, and the TiB reinforcing phase is dispersed in the matrix in the form of whiskers. The aspect ratio of the whiskers is controlled to be 3 to 10 after forging and hot working.
4. A method for preparing a heat-resistant titanium-based composite rod, characterized in that, The material of the rod is the heat-resistant titanium-based composite material as described in any one of claims 1-3, and the preparation method includes the following steps: S1. The components of the heat-resistant titanium-based composite material are uniformly mixed in a mixer, pressed into single electrodes, and welded together to form a melting electrode. The titanium-based composite material ingot is prepared by at least three vacuum self-consuming arc melting processes. The ingot is then subjected to riser, ingot bottom sawing, and peeling treatment to obtain the finished ingot. S2. The finished ingot obtained in step S1 is subjected to 1 to 2 forging cycles at 1150℃~1200℃ using a high-speed forging machine. The holding time is the diameter of the finished ingot × 0.8 min / mm. Each forging cycle adopts the upsetting and drawing process and the total forging ratio of upsetting and drawing in a single forging cycle is not less than 7.
0. The deformation speed is controlled at 20~50 mm / s, and the final forging temperature is not lower than 900℃. After forging, it is air-cooled to obtain the forged billet. S3, the forged billet obtained in step S2 is subjected to T... β -60℃~T β The forging process involves 1 to 4 forgings within a temperature range of +100℃, with 2 to 6 deformation passes per forging. The deformation amount per pass is controlled at 5% to 30%, and the final forging temperature is not lower than 800℃. This process yields semi-finished bars, which are then surface-machined to obtain small-diameter bars with a diameter of 100mm or less. S4. Heat-treat the small-sized rods obtained in step S3, and then machine them to obtain heat-resistant titanium-based composite material rods.
5. The method for preparing the heat-resistant titanium-based composite rod as described in claim 4, characterized in that, In step S2, the initial forging temperature of the billet forging is 1150℃, and two upsetting and drawing processes are carried out. The total forging ratio of each upsetting and drawing process is 7.0 to 7.5, the deformation speed is 30 to 40 mm / s, and the final forging temperature is not lower than 920℃. After forging, the billet is air-cooled to room temperature and then put into the furnace for heating for the next upsetting and drawing process.
6. The method for preparing the heat-resistant titanium-based composite rod as described in claim 4, characterized in that, In step S3, the precision forging is carried out using a radial precision forging machine at a temperature of 1050℃~1120℃. The forging is performed in two passes, with 4 to 5 passes per pass. The deformation amount per pass is controlled at 10%~25%, and the final forging temperature is not lower than 820℃. The diameter of the resulting small-diameter bar is Φ30mm~Φ100mm.
7. The method for preparing the heat-resistant titanium-based composite rod as described in claim 4, characterized in that, In step S4, the heat treatment is either single-stage annealing or solution aging. Single-stage annealing includes the following steps: holding at 600℃~850℃ for 4~8 hours followed by air cooling. Solution aging includes the following steps: first... β -120℃~T β After holding at +80℃ for 0.5–2 hours, air cool or quench water cool, then hold at 600℃–800℃ for 4–8 hours before air cooling.
8. The method for preparing the heat-resistant titanium-based composite rod as described in claim 7, characterized in that, In step S4, the solution aging treatment specifically includes the following steps: holding at 1000℃~1050℃ for 1 hour followed by water quenching, then heating to 700℃ and holding for 4 hours followed by air cooling; or holding at 1025℃ for 1.5 hours followed by furnace cooling, then heating to 1010℃ and holding for 1 hour followed by water quenching, then heating to 700℃ and holding for 4 hours followed by air cooling.
9. A heat-resistant titanium-based composite rod prepared by the method according to any one of claims 4 to 8, characterized in that, The finished bar stock shall have a maximum diameter of Φ100mm, an elongation at room temperature of not less than 8%, a tensile strength at 650℃ of not less than 650MPa and an elongation at break of not less than 20%, and a reduction of area of not less than 55%.